Exploring the relationship between attitude towards laptop usage and laptop utilisation: a preliminary study among Malaysian science and mathematics teachers - Moses, Priscilla; Wong, Su Luan; Abu Bakar, Kamariah; Mahmud, Rosnaini (Universiti Putra Malaysia Press, 2012)
Realising the importance of ICT in the education system, the Malaysian Ministry of Education introduced the laptop initiative to integrate ICT into the students’ learning environment. The laptop provides a unique feature which allows the integration of ICT into the education at anytime and anywhere. Based on the review of literature, teachers’ attitude is seen as one of the significant indicators in influencing teacher’s laptop utilisation. The objectives of this study were to explore the teachers’ levels of laptop utilisation in terms of teaching and learning processes (TLP), lesson preparation and planning (LPP); teachers’ level of attitude towards laptop usage; and also to examine the relationship between teachers’ attitude towards laptop usage and laptop utilisation. Survey questionnaires were administered to 38 secondary school Mathematics and Science teachers. The results reported that the teachers’ laptop utilisation was at the moderate level (TLP: M = 3.13, S.D. = 5.56 and LPP: M = 3.09, S.D. = 4.68) and these teachers showed positive attitude towards the laptop (M = 3.84, S.D. = 13.04). Furthermore, the findings also revealed that there was a significant positive correlation between teachers’ attitude towards laptop usage and laptop utilisation (TLP: r = .69 and LPP: r = .44).